Komodifikasi Hadis dalam Media Sosial: Analisis Promosi Air Minum Ajwa di Era Digital - Fakhri Ilham Syarifudin (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2026)
This study examines the phenomenon of using hadith in the marketing of Ajwa Drinking Water as a form of religious commodification in the digital era. The research focuses on the use of the hadith, “The best of people are those who are most beneficial to others,” in the promotion of Ajwa drinking water products marketed through social media. This study employs a qualitative method with a hadith analysis approach and the study of contemporary religious movements. The data were obtained from product promotional posts, hadith literature, and studies on the commodification of religion and shifts in religious authority. The findings reveal that the hadith, which originally functioned as a guideline for social ethics, undergoes a transformation of meaning when used as a branding element for commercial products. The use of hadith in marketing creates a symbolic association between product consumption and expressions of piety, thereby reducing religion into an instrument of commercial value. Furthermore, this study finds a shift in authority from religious scholars to market authority, where commercial brands assume the role of conveying and interpreting religious messages. This study emphasizes the importance of caution in the use of hadith texts in public spaces so that religious values are not instrumentally exploited for economic interests.